2018
DOI: 10.1155/2018/4387506
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Long-Lasting Insecticide Treated Nets and Parasitaemia at 6 Months after a Mass Distribution Exercise among Households in Mbarara Municipality, Uganda: A Cross-Sectional Community Based Study

Abstract: Background Utilization of long-lasting insecticide treated nets (LLINs) after free and mass distribution exercise has not been adequately studied. The objectives of this study were to assess ownership and utilization of LLINs following a mass distribution campaign in a Ugandan urban municipality. Methods We conducted a cross-sectional study in western Uganda among households with children under 5 years, at 6 months after a mass LLIN distribution exercise. We administered a questionnaire to measure LLIN ownersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 27 publications
5
25
3
Order By: Relevance
“…Bed net utilization was signi cantly associated with the presence of either a pregnant mother or under ve years aged children in the household among internally displaced households in the Democratic Republic of Congo (16), household members in the Budondo sub-country in Uganda (28), a national community based survey in Madagascar (30). In agreement with our nding, bed net utilization by SAC was not affected by the presence of pregnant mother or children aged less than ve years in the household in Malawi (45) and general population in Yemen (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bed net utilization was signi cantly associated with the presence of either a pregnant mother or under ve years aged children in the household among internally displaced households in the Democratic Republic of Congo (16), household members in the Budondo sub-country in Uganda (28), a national community based survey in Madagascar (30). In agreement with our nding, bed net utilization by SAC was not affected by the presence of pregnant mother or children aged less than ve years in the household in Malawi (45) and general population in Yemen (38).…”
Section: Discussionmentioning
confidence: 99%
“…In strati ed analysis of studies targeting the general population as well as studies focused on SAC reveal that the burden of malaria was higher among this group of the population in Ethiopia (13)(14)(15). The consequence of malaria infection on children suffering affects their physical growth, mental development and overall economic development of the country (16,17). Above all, they were responsible for about 60% of infection to mosquito vector for the transmission of the disease in all seasons (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strati ed analysis of studies targeting the general population, as well as studies focused on SAC, revealed that the burden of malaria was higher among this group of the population in Ethiopia [13][14][15]. The consequence of malaria infection on children affects their physical growth, mental development and overall economic development of the country [16,17]. Above all, they were responsible for about 60% of infection to the mosquito vector for the transmission of the disease in all seasons [18].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria continues to be the most prevalent parasitic infection responsible for high burden of disease and deaths in low-income countries. About half of the world's population lives in malaria endemic areas and pregnant women are considered as the high-risk group for malaria transmission (1). As a result nearly 435,000 deaths annually and 219 million malaria cases were reported in 2017 globally.…”
Section: Introductionmentioning
confidence: 99%